Situation Report: Poland, 25 May 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ideological Troubles of Party Scholars Radio Broadcasts to Foreign Countries Changes in Passport Fees and Foreign Currency Allowances The New Law on Customs Duties Iranian Premier's Visit: Accord on Oil Deliveries Poland Enters Icelandic Fishing Limits Dispute US Bank President in Poland: Financing of Huge Cooper Development Project Discussed